Molecular Dynamics Simulation of Cylindrical Droplets - Yan, H.; Huang, D.C. (Asian Journal of Chemistry, 2011)
Study of the surface properties is of great interest from the standpoint of both fundamental and practice. In this paper cylindrical droplets in nanoscale are investigated. A method to determine the surface tension is given by Gibbs theory of capillarity. The scheme is carried out by molecular dynamics simulation. The effect of temperature and cutoff distance are studied. It is find that surface tension decreases with increasing temperature and corresponding quantities sensitively depend on the interaction potential.